Compensation after treatment for anterior cruciate ligament injuries: a review of compensation claims in Norway from 2005 to 2015 - Randsborg, Per-Henrik (Knee Surg Sports Traumatol Arthrosc, 2017)
PURPOSE: To assess the most common reasons for complaints following anterior cruciate ligament (ACL) injuries reported to the Norwegian System of Patient Injury Compensation (NPE), and to view these complaints in light of the ACL reconstructions (ACL-Rs) reported to the Norwegian Knee Ligament Registry (NKLR). METHOD: Data from the NPE and the NKLR were collected for the study period (2005–2015). The age and gender and type of complaint and reason for granted compensation were collected from the NPE, while the graft choice and total number of ACL-R were collected from the NKLR. Risk for successful grant was estimated for graft type. RESULTS: 18,810 primary ACL-Rs were reported to the NKLR during the study period. A hamstring graft was used in 12,437 (66.1%) but the bone-patellar tendon-bone (BPTB) became the graft of choice at the end of the study period. 240 patients filed a complaint to the NPE, of which 101 were granted compensation. The odds ratio for a claim being granted following a hamstring graft was 2.9 compared to that of a BPTB graft (p = 0.002) The most common reason for compensation was a hospital-acquired infection in 39 patients (38.6%) followed by inadequate surgical technique (27, 26.7%) and delayed diagnosis (13, 12.9%). Of the 39 patients with infection, 27 had received a hamstring graft and six a BPTB graft (two patients were not reconstructed, data missing for three patients). Of the 27 patients who were granted compensation due to inadequate surgical technique, 24 had received a hamstring graft and three a BPTB graft. CONCLUSION: Infection and inadequate surgical technique are the most common causes for granted compensation from the NPE following ACL injury. Hamstring grafts have a threefold risk of complication that yields compensation from the NPE compared to BPTB grafts. This information is relevant for patients and surgeons when choosing graft type. The trend of increased use of BPTB grafts is warranted based on the results from this study. LEVEL OF EVIDENCE: Level III.